Enhancing the Drag Reduction Phenomenon within a Rotating Disk Apparatus Using Polymer-Surfactant Additives - Rashed, Musaab K.; Mohamad Amran, Mohd Salleh; Abdulbari, Hayder A.; M. Halim Shah, Ismail (MDPI, 2016)
Pipelines and tubes play important roles in transporting economic liquids, such as water, petroleum derivatives, and crude oil. However, turbulence reduces the initial flow rate at which liquids are pumped, thereby making liquid transportation through pipelines inefficient. This study focuses on enhancing the drag reduction (DR) phenomenon within a rotating disk apparatus (RDA) using polymer-surfactant additives. The complex mixture of polyisobutylene (PIB) and sodium dioctyl sulfosuccinate (SDS) was used. These materials were tested individually and as a complex mixture in RDA at various concentrations and rotational speeds (rpm). The morphology of this complex was investigated using transmission electronic microscopy (TEM). The reduction of the degradation level caused by the continuous circulation of surfactant additives in RDA could improve the long-term DR level. Experimental result shows that the maximum %DR of the complex mixture was 21.455% at 3000 rpm, while the PIB and SDS were 19.197% and 8.03%, respectively. Therefore, the complex mixture had better performance than these substances alone and were highly dependent on the alkyl chain of the surfactant.